Upholding dignity during a pandemic via Twitter [version 2; peer review: 1 approved, 2 approved with reservations] - Tracey O'Sullivan; Sarah Fraser; Michael Mulvey (F1000Research)
Background This article investigates how people invoked the concept of dignity on Twitter (X) during the first year of the COVID-19 pandemic, with a secondary focus on mentions of dignity in the context of older adults and ageing. Methods We report the results of a study that combines text analytic and interpretive approaches to analyze word clusters and dignity-based themes in a cross-national sample of 1,946 original Twitter (X) messages posted in 2020. Results The study finds that dignity discourse on Twitter advances five major themes: (a) recognizing dignity as a fundamental right, (b) upholding the dignity of essential workers, (c) preserving the dignity of at-risk populations, (d) preventing cascading disasters that exacerbate dignity’s decline, and (e) attending to death, dignity, and the sanctity of life. Conclusions Within the discourse, dignity emerged as a right and a policy target (improving or maximizing dignity in various groups). Further, the posts focusing on older adults and dignity demonstrated that the impacts of COVID-19 disproportionately impacted older adults, particularly those with greater care needs and financial insecurity or lower socioeconomic status.